Conventional tissue culture compared with rapid immunofluorescence for identifying Chlamydia trachomatis in specimens from patients attending a genitourinary clinic. Issue 6 (December 1985) - Teare, E L; Sexton, C; Lim, F; McManus, T; Cuttley, A H; Hodgson, J
Abstract : Specimens collected from 182 patients with histories suggesting chlamydial disease were examined by conventional culture and direct immunofluorescence techniques. Chlamydia trachomatis was identified by both methods in 57% of all patients. There was no significant difference between the two methods in detecting C trachomatis. Where a tissue culture service is not already established, cost analysis in individual departments may justify the use of the immunofluorescence method.